Manajemen Mutu Sekolah Studi Komparatif SMAN 1 Dan SMAN 5 Kota Bengkulu - Putri Kartiwi, Asti; Resi Yusriani (Manajer Pendididikan, 2023)
The purpose of this study is to analyze the comparison of school quality management between Senior High School Number 1 and 5 Bengkulu City. This research method is descriptive qualitative, data collection techniques are by observation, interviews and documentation, data analysis by data reduction, data presentation and conclusion. Bengkulu Province; 2) Policy planning involves school principals, school vice principals, teachers, and committees to formulate policy plans; 3) Implementation carried out by each school in accordance with the plan, namely compiling curriculum structures, competency standards, learning load estimates, making syllabus, and making educational calendars, establishing competence standard and fundamental competence, selecting appropriate learning materials; 4) Quality evaluation is determined by: curriculum structure, competency standards, learning load estimates, syllabus making, management evaluation, and assessment evaluation according to the 13 revisions of the curriculum, as well as reviewing policies that are found to be non-conformances.